Experiment on MICP-solidified calcareous sand with different rubber particle contents and sizes - Xu, Xinxing; Yan, Xinning (Frontiers in Materials, 2024)
Microbially induced calcite precipitation (MICP) is a new environmentally friendly technology which ability to improve the mechanical properties of calcareous sand. Rubber is a high compressibility material with a higher damping ratio than calcareous sand. In this study, calcareous sand was replaced by equal volume contents (0%, 1%, 3%, 5%, 7%, 9%) and different sizes (0-1, 1-2, 2-3 mm) rubber, and a series of water absorption and unconfined compressive strength (UCS) tests were conducted on MICP solidified rubber-calcareous sand (MRS). The results showed that the water absorption is reduced when the rubber content is larger. The UCS of 0-1 mm MRS decreased with the increase in rubber content. For 1-2 mm and 2-3 mm MRS, the UCS was improved by 11.30% and 15.69% compared with the clean sand. Adding rubber promoted the formation of calcium carbonate, but the strength and stiffness of rubber particles were lower than the calcareous sand. Therefore, higher rubber content weakened the sand frame bearing system, and the UCS decreased when the rubber content was more than 5%. Moreover, a large amount of 0-1 mm rubber led to the increase of transverse deformation of the samples, which caused the acceleration of the destruction of the sand structure. The water absorption of 0-1 mm MRS was higher than that of 1-2 mm and 2-3 mm MRS, but the UCS of 0-1 mm MRS was lower. The best rubber size is 1-2 mm and 2-3 mm, and the best rubber content is 3-5%. The outcome of this study may in the authors’ view prove beneficial in improving the strength of calcareous sand when it is reinforced by MICP combined rubber.